FcγRIIIa-dependent IFN-γ release in whole blood assay is predictive of therapeutic IgG1 antibodies safety. Issue 6 (18th August 2018) - Alakhras, Nada S.; Qiu, Jiabin; Rocha, Guilherme V.; Witcher, Derrick R.; Koester, Anja; You, Jinsam; Schaer, David A.; Holmgaard, Rikke B.; Driscoll, Kyla; Willy, Jeffrey A.; Malherbe, Laurent P.
ABSTRACT: Immunomodulatory monoclonal IgG1 antibodies developed for cancer and autoimmune disease have an inherent risk of systemic release of pro-inflammatory cytokines. In vitro cytokine release assays are currently used to predict cytokine release syndrome (CRS) risk, but the validation of these preclinical tools suffers from the limited number of characterized CRS-inducing IgG1 antibodies and the poor understanding of the mechanisms regulating cytokine release. Here, we incubated human whole blood from naïve healthy volunteers with four monoclonal IgG1 antibodies with different proven or predicted capacity to elicit CRS in clinic and measured cytokine release using a multiplex assay. We found that, in contrast to anti-CD52 antibodies (Campath-1H homolog) that elicited high level of multiple inflammatory cytokines from human blood cells in vitro, other IgG1 antibodies with CRS-inducing potential consistently induced release of a single tested cytokine, interferon (IFN)-γ, with a smaller magnitude than Campath. IFN-γ expression was observed as early as 2–4 h after incubation, mediated by natural killer cells, and dependent upon tumor necrosis factor and FcγRIII. Importantly, the magnitude of the IFN-γ response elicited by IgG1 antibodies with CRS-inducing potential was determined by donor FcγRIIIa-V158F polymorphism. Overall, our results highlight the importance of FcγRIIIa-dependent IFN-γ release in preclinical cytokine release assay for the prediction of CRS risk associated with therapeutic IgG1 antibodies.